2015
DOI: 10.5539/ibr.v8n9p135
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Organizational Performance through Effective Mission Statement

Abstract: The mission statement is a critical and an integral part of the organization as an entity and the operating plan, which has become a unique vehicle through which the organization in the business world, articulates it strategic intent to exist, survive, grow and how it relates with stakeholders around it and including the wider society. The important question to ask is whether or not the existence of a mission statement is associated with or influences organizational performance? The findings from the various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…The negative relationship between company mission and strategic performance may be due to poor communication or employees are not aware of the company mission during strategy formulation. The results from this study negate the findings of other several researchers who found a positive and significant association between mission and organisational performance, (Sandada, 2014;Mosoma, 2014;Ekpe et al, 2015;Forbes & Seena, 2006;Sidhu, 2003). However, the findings from this study support the previous studies that found no positive and significant relationship between mission and performance (Bart & Baetz, 1998;O'Gorman & Doran, 1999;Vandijck et al, 2007).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The negative relationship between company mission and strategic performance may be due to poor communication or employees are not aware of the company mission during strategy formulation. The results from this study negate the findings of other several researchers who found a positive and significant association between mission and organisational performance, (Sandada, 2014;Mosoma, 2014;Ekpe et al, 2015;Forbes & Seena, 2006;Sidhu, 2003). However, the findings from this study support the previous studies that found no positive and significant relationship between mission and performance (Bart & Baetz, 1998;O'Gorman & Doran, 1999;Vandijck et al, 2007).…”
Section: Discussioncontrasting
confidence: 95%
“…Odita & Bello (2015) concluded that the mission dimension of strategic intent has a significant and positive relationship with organisational performance in the banking industry in Nigeria. Ekpe et al (2015) observed that firm mission is positively related to organisational performance. Studying eighteen not for profit hospitals, Forbes & Seena (2006) found a robust evidence of the impact of mission statement on performance.…”
Section: Influence Of Strategy Formulation Drivers On Strategic Perfomentioning
confidence: 99%
“…Deephouse goes further by arguing that mission statements also serve crucial internal and external roles. To date, the vast spectrum of existing studies in mission statement research explores important topics such as the influence of organizational size (O'Gorman and Doran, 1999; King et al , 2014a, b); corporate identity (Leuthesser and Kohli, 1997, 2015); the reflection of trends in ethics and corporate social responsibility (Jung and Pompper, 2014; King et al , 2010; Wilburn and Wilburn, 2014, 2015; Fifka et al , 2018); global initiatives and international comparative analysis (Mion et al , 2021; King et al , 2011, 2014b; Mas-Machuca et al , 2017; Panda and Gupta, 2003; Sengupta and Sahay, 2017); the importance of stakeholder representation (Bartkus and Glassman, 2008); the link between organizational performance and effective mission statements (Atrill et al , 2005; Bart and Baetz, 2002; Baetz and Kenneth, 1998; Bart et al , 2001; Bart and Hupfer, 2004; Ekpe et al , 2015; Germain and Cooper, 1990; Green and Medlin, 2003; value creation (Zerfass and Viertmann, 2017); member motivation and implementation (Rey and Bastons, 2018) and ensuring diversity, equity, and inclusion in organizational mission statements (Swenor and Meeks, 2019; Ortega et al , 2020). The breadth of existing mission research also spans a broad cross-section of specific industries and sectors including research of mission statements for commercial airlines (Law and Breznik, 2018; Kemp and Dwyer, 2003); cruise lines (Penco et al , 2017); health-care organizations (Bart, 2002; Bart and Hupfer, 2004, Kamran and Cin, 2020); educational services organizations and institutions (Bayrak, 2020; Yob et al , 2016; Lineham, 2013; Woodrow, 2006; Davis et al , 2007; Genç, 2012; Palmer and Short, 2008); non-profit organizations (Bart, 2000; Macedo et al , 2016; Pandey et al , 2017; Kirk and Nolan, 2010; Sheehan, 1996); public organizations (Desmidt, 2016) and philanthropic organizations (Kesberg and Keller, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to delineating strategic intent for its existence across all levels, mission statements relate to both internal and external stakeholders and are sensitive to employees, customers, the general market and wider society in order to survive, thrive and achieve higher performance (Anitsal et al, 2012(Anitsal et al, , 2013Cochran et al, 2008;Alegre et al, 2018;Mullane, 2002). Notably, effective mission statements provide organizations with a focus and a strategy for the future and a sense of direction and purpose which in times of change and growth can be an anchor and a guide in decision-making (Ekpe et al, 2015). Similar claims are historically prevalent in mission statement research, with the mission statement often noted as an essential first step in the strategic management process (Drucker, 1974;David, 1989;Staples and Black, 1984;Pearce, 1982;Abell, 1980;Bartkus and Glassman, 2008).…”
Section: The Influence Of Covid-19 On Mission and Crisis Communicatio...mentioning
confidence: 99%
“…There are numerous methods to measure the effectiveness of an organisation. According to scholars, effectiveness is measured by a simple strategy: if the mission, goals, and objectives are met, that company is efficiently running (Ekpe, 2015;Jurevicius, 2013;William, 2012). Several studies on occupational stress and productivity have been conducted in Sri Lanka (Aroosiya & Ali, 2016;Ehsan & Ali, 2019;Silva & Thilakasiri, 2014).…”
Section: Measures For Productivitymentioning
confidence: 99%